2019
DOI: 10.1177/0883073819885724
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Palsy in Children With Congenital Zika Syndrome: A 2-Year Neurodevelopmental Follow-up

Abstract: Objective: To describe the 2-year neurodevelopmental outcome in children with cerebral palsy associated with congenital Zika (CZ) and explore variables associated with a more severe presentation. Methods: Data on 69 children with cerebral palsy associated with CZ, followed in a neurorehabilitation hospital, who consecutively attended the neurodevelopmental assessment at 2 years of age, were collected. Bayley III Scales of Infant and Toddler Development, Hammersmith Infant Neurological Examination, and Gross Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 21 publications
3
57
0
4
Order By: Relevance
“…The overall quality of the selected studies is considered good, with high (12/15; 80%) [8][9][10][11][12][14][15][16][17][18][19]21 or moderate (3/15; 20%) 13,20,22 methodological quality according to the Newcastle-Ottawa scale (Table S1, Supplementary file). None of the studies described the intra-and inter-assay variations of the serological and molecular tests used in diagnosing ZIKV infection.…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall quality of the selected studies is considered good, with high (12/15; 80%) [8][9][10][11][12][14][15][16][17][18][19]21 or moderate (3/15; 20%) 13,20,22 methodological quality according to the Newcastle-Ottawa scale (Table S1, Supplementary file). None of the studies described the intra-and inter-assay variations of the serological and molecular tests used in diagnosing ZIKV infection.…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%
“…The remaining 15 studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were critically analyzed and the information of interest was extracted. Among the selected studies, 13 [8][9][10][11][12][15][16][17][18][19][20][21][22] are articles published in specialized journals, and 2 are theses from Brazilian public universities (Universidade Federal de Pernambuco 13 and Universidade Federal Fluminense 14 ). One study 17 was not included in the meta-analysis because it used the same patients of the study 16 with different follow-up times.…”
Section: Study Inclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence on CZS that was emerging at the time of this study highlighted the similarities of the physical presentation of CZS to those of CP. More recent literature has further described the overlapping between CZS and CP [35][36][37]. The review of the literature and findings of the social and economic impact study also suggested that there are similarities between CP and CZS, particularly in terms of needs and unmet needs of the caregiver.…”
Section: C)mentioning
confidence: 96%